Efficacy of Two Inducing Agents, PG and DOM+SGNRH on the Induced Breeding of the Major Carp, Kalibaus (Labeo calbasu) - Bhuiyan, Abdus Salam; Akhter, Jesmin; Mushahida-Al-Noor, Syeda (Our Nature, 2013)
The present study was conducted to compare the efficacy of two inducing agents PG and DOM+SGnRH on the induced breading of Labeo calbasu. Three breeding trials were done with PG hormone as treatment 1 and three breeding trials were done with DOM + SGnRH as treatment 2. Total 8 pairs of brood fishes were collected from the Halda River and from the Jamuna River and reared in the pond, providing special diet up to their maturation. In case of treatment 1, the females were injected 1.5mg PG/kg body weight as initial dose and 6 mg PG/kg body weight as resolving dose. On the other hand, males were administered at the rate of 1.5 mg PG/kg body weight. On the contrary in case of treatment 2, the females and males were injected DOM+SGnRH at the rate of 12 mg/kg body weight and 3 mg/kg body weight respectively. In case of treatment 1, the intervals between initial and resolving dose were 5 hours and ovulation took place within 6 hours after the resolving doses. In case of treatment 2, only initial dose is required and ovulation occurred respectively within 7 hours. The mean rates of ovulation, fertilization and hatching were 100, 77.36 and 74.5%, respectively in treatment 1. The mean rates of ovulation, fertilization and hatching were 83.33, 63.83 and 59.66%, respectively in treatment 2. DOI: http://dx.doi.org/10.3126/on.v11i1.8239 Our Nature Vol.11(1) 2013: 17-24